Is there no place on earth for me? - Sheehan, Susan, 1937- (Vintage Books, a division of Random House LLC, 2014)
Recounts the lonely, harrowing life of a diagnosed schizophrenic Sylvia Frumkin, whose experience has included frequent hospitalizations from childhood on, bouts with insulin comas, electroshock treatments, and drug therapy.